2011
DOI: 10.1002/cncr.26134
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results and risk factors of proton and carbon ion therapy for hepatocellular carcinoma

Abstract: BACKGROUND:The objective of this study was to evaluate the clinical outcome of proton and carbon ion therapy for hepatocellular carcinoma (HCC). METHODS: In total, 343 consecutive patients with 386 tumors, including 242 patients (with 278 tumors) who received proton therapy and 101 patients (with 108 tumors) who received carbon ion therapy, were treated on 8 different protocols of proton therapy (52.8-84.0 gray equivalents [GyE] in 4-38 fractions) and on 4 different protocols of carbon ion therapy (52.8-76.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 40 publications
6
116
1
3
Order By: Relevance
“…In addition, the incidence rates of RILD at 3 and 6 months after CIRT were considered to be low in the current study. In a study comparing CIRT and proton therapy for HCC, Komatsu et al29 observed no severe adverse effects, including effects in the liver for patients treated with CIRT. These results suggest that the high dose‐concentrating ability of the carbon‐ion beam offsets the higher biological effect of high linear energy transfer radiation on healthy tissue damage, and this allows the benefits of high linear energy transfer radiation to affect primarily the target.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence rates of RILD at 3 and 6 months after CIRT were considered to be low in the current study. In a study comparing CIRT and proton therapy for HCC, Komatsu et al29 observed no severe adverse effects, including effects in the liver for patients treated with CIRT. These results suggest that the high dose‐concentrating ability of the carbon‐ion beam offsets the higher biological effect of high linear energy transfer radiation on healthy tissue damage, and this allows the benefits of high linear energy transfer radiation to affect primarily the target.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Komatsu et al reported on the retrospective review of 343 consecutive patients with HCC treated at the Hyogo Ion Beam Medical Center with proton or carbon ion therapies (35). For the 285 patients for which both proton and carbon ion beams were available, treatment planning with both modalities were performed and the better treatment plan was selected based on dosimetric criteria.…”
Section: Clinical Outcomes Of Hcc Treated With Proton Radiotherapymentioning
confidence: 99%
“…NTCP modeling may have great potential in risk adapted dose prescription of SBRT of liver tumors. It may be employed in comparative treatment planning studies between particle-and photon-based SBRT for optimal selection of candidates for particle beam therapy, that may offer ideal dose distribution and favorable relative biological efficacy [20,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%